E-Module of Physics Science Integrated with Sustainable Development Goals to Enhance Students' Environmental Literacy - Hestiningtyas Yuli Pratiwi; Sudi Dul Aji; Arief Rahman Hakim; Chandra Sundaygara; Anatolia Gurtin; Muhammad Nur Hudha (Universitas Lambung Mangkurat, 2023)
This study aims to produce a product of an electronic module on the subject of energy to enhance students' environmental literacy. This research was a research and development (R&D) using the ADDIE development model which includes: 1) the initial needs analysis stage to determine the needs of students and teachers, 2) the design stage which included collecting references, instruments and designing and creating an e-module of the science of physics integrated Sustainable Development Goals (SDGs), 3) the development of e-modules was carried out using the Canva application, Fliphtml and validation of material and media experts, 4) small-scale trials conducting interviews with students and teachers to obtain qualitative data in-depth, 5) evaluation from users, namely students and subject teachers. The assessment included 1) a Media expert test; 2) a material expert test; 3) user tests; 4) a small-scale test. The results of this study showed that: (1) the SDGs integrated science e-module was produced to enhance students' environmental literacy (2) the quality of the science e-module for students was developed according to material experts and media experts to have very good quality (VG) with the ideal percentage of each 83.00% and 98.00%. (3) the teacher's response to the student module is Very Good (VG) with an ideal percentage of 98%. Meanwhile, the student's response to the student's science e-module is Strongly Agree with an ideal percentage of 83.00%. Based on the results of this study, it can be concluded that the Science E-Module Integrated to SDGs has met the criteria of being feasible and effective for enhancing students' environmental literacy skills seen from the responses of media experts, material expert responses, students’ responses and trials.